The Effects of Accounting Information System Antecedents and Effectiveness on Local Government Financial Performance in Tanzania - Chalu, Henry (University of Dar es Salaam Library Journal, 2025)
The nature of the relationship between Accounting Information Systems (AIS) and organisational performance has been the subject of numerous studies due to technological advancements and the computerisation of AIS. However, the results have been mixed and inconclusive. This paper is focused on assessing the effects of AIS antecedents and AIS effectiveness on the financial performance of the LGAs in Tanzania. The focus on antecedents of AIS is on five variables, namely accounting policies, auditing effectiveness, computerisation of AIS, management support, and skilled human resources. Regarding AIS effectiveness, the focus is on two key measurements: accounting information quality and system quality. Data was collected using questionnaires distributed to 179 LGA officials in 11 LGAs in Tanzania. The data collected was analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM), and the results show that accounting information quality and systems quality have a positive influence on financial performance. In addition, system quality was found to have a significant mediating effect. Regarding the influence of antecedents, the study's findings reveal that accounting policies and the computerisation of AIS are negatively related to AIS effectiveness, as well as to financial performance. Generally, the study concludes that to improve financial performance at LGAs, accounting information quality and system quality should be considered relevant. In addition, it concludes that accounting policies and computerisation of AIS are crucial matters for AIS effectiveness and LGA financial performance because they tend to reduce improvement if not handled carefully. https://dx.doi.org/10.4314/udslj.v20i1.14